Dairy Business Analysis Project: 2002 Financial Summary - Albert de Vries; Russell Giesy; L. Ely; A. de Araujo; A. Andreasen; Brent Broaddus; Shepard Eubanks; Doug Mayo; P. Miller; Travis Seawright; Chris Vann (EDIS, 2004)
This publication is a summary of the financial performance of Florida dairy businesses in the year 2002. It is intended for general use by dairy farmers, the allied industry, and government, and educational professionals. This document is AN149, one of a series of the Department of Animal Sciences, Florida Cooperative Extension Service, UF/IFAS. Published June 2004.